Factors influencing the continuance intention of the women’s health WeChat public account: an integrated model of UTAUT2 and HBM - Min, Hewei; Li, Jiaheng; Di, Menglei; Huang, Shuhong; Sun, Xinying; Li, Tao; Wu, Yibo (Frontiers in Public Health, 2024)
Objective: This study aims to construct a comprehensive model, delving into the key factors influencing women's continuance intention of the women's health public accounts from the perspectives of perceived health threats, individual abilities, and technological perceptions. Method: An online survey was conducted among women receiving gynecological care at a certain hospital to gauge their willingness for sustained use of the women's health WeChat public accounts. Through structural equation modeling, the study investigated the influencing factors on women's sustained intention to use the women's health WeChat public accounts.Results: The study included a total of 853 adult women. Among them, 241 (28.3%) women had followed women's health official accounts in the past but do not currently follow them, 240 (28.1%) women had followed women's health official accounts in the past and are still following them, and 372 (43.6%) women had never followed women's health official accounts. Currently, 240 women are still browsing women's health public accounts, 52 of whom read women's health public accounts every day, and most of them read women's health public accounts for 10-20 minutes at a time (100, 11.7%). The results of the structural equation model revealed that performance expectancy, social influence, hedonic motivation, habit, and e-health literacy had significantly positive effects on women's sustained intention to use the public accounts. E-health literacy and self-efficacy indirectly influenced sustained intention by affecting performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit. The effect sizes of e-health literacy on performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit were 0.244 (P＜0.001), 0.316 (P＜0.001), 0.188 (P＜0.001), 0.226(P＜0.001), 0.154 (P＜0.001), and 0.073 (P=0.046). And the effect sizes of self-efficacy on performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit were 0.502 (P＜0.001), 0.559 (P＜0.001), 0.454 (P＜0.001), 0.662 (P＜0.001), 0.707 (P＜0.001), and 0.682 (P＜0.001). Additionally, perceived severity and perceived susceptibility indirectly affected sustained intention by influencing performance expectancy and social influence. The effect sizes of perceived severity on performance expectancy and social influence were 0.223 (P＜0.001) and 0.146 (P＜0.001). And the effect size of perceived susceptibility on social influence was 0.069 (P=0.042).